Prevalence and factors associated with teenage pregnancy in Nepal - Bhusal, Hari Prasad; Neupane, Sabitra; Bhusal, Simran (International Journal Of Community Medicine And Public Health, 2025)
Background: Every year, approximately 16 million adolescents give birth globally, accounting for 11% of all births worldwide. 95% of these births take place in low- and middle-income nations. The objective of this study was to assess the prevalence and contributing factors related to teenage pregnancy in Nepal. Methods: Standardized data was sourced from the NDHS 2016. This cross-sectional survey was representative of the national population, utilizing a multistage cluster sampling method. Data collection was carried out through three sets of structured questionnaires. Authorization for data usage has been secured from the relevant agency. Statistical analyses were performed using STATA. Results: NDHS 2016 reported a teenage pregnancy prevalence was 16.7%. Among those aged 15 to 19, 61% were married. The incidence of teenage pregnancy was notably low among Brahmin/Chhetri (11.5%), highest among Muslims (22.7%), and lowest among Buddhists (12.8%). The middle wealth category exhibited the highest prevalence. Additionally, teenage pregnancy was more prevalent in rural areas, particularly in Terai. A significant association was found between the age of respondents and teenage pregnancy and the employment status of respondents (p<0.05). However, the educational attainment of respondents did not demonstrate any significant association with teenage pregnancy. Conclusions: The prevalence was highest among the Madhesi community followed by Muslims. The age of the respondents or marriage before the age of 19, economic status of the respondents, rural place of residence, and occupation of the respondents were significantly associated with teenage pregnancy in Nepal.